Determining cause and effect relations between strategy and business processes of the company - T. V. Natalyina (Вестник СибАДИ)
The author has considered an approach to forming key indicators of efficiency for companies, based on determining cause and effect relations between strategy and business processes. There is suggested and tested on the basis of leather goods’ factory a method of cascading purposes and strategies till the level of business processes with educing key indicators of efficiency, ensuring the formation of an ordered pattern of the company development’s process.